Inhibition of cell proliferation in gastric cancer cell lines on exposure to rubriflordilactone A (Bangladesh Journal of Pharmacology, 2015)
The present study investigates the effect of rubriflordilactone A on the viability and its underlying mechanism in gastric cancer cell lines (SNU-1 and SNU-5) and normal gastric epithelial cell line (GES?1). Incubation of the gastric cancer and non cancer cell lines in acidic media led to reduction in the viability of the non cancer cells without any effect on cancer cells. Apoptosis in SNU-1 and SNU-5 cells was induced on exposure to rubriflordilactone A after 48 hours compared to the control cells (p